EFEKTIVITAS PENGGUNAAN APLIKASI E-FLEARN DALAM MENUNJANG KEGIATAN PEMBELAJARAN MAHASISWA PTIK - Heidy Francis Rantung; Rissal Efendi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In the era of technological advancement, the education sector has undergone significant transformation through the integration of information and communication technology (ICT). One manifestation of this integration is the implementation of e-learning, which enables a flexible and interactive learning process. Universitas Kristen Satya Wacana (UKSW) has adopted an e-learning platform called Flexible Learning (Flearn), developed by the Bureau of Technology and Information Systems (BTSI). Flearn offers various features, including access to learning materials, assignment submissions, discussion forums, and the administration of online exams or quizzes, thereby supporting efficient, effective, and engaging learning. The Informatics and Computer Engineering Education (PTIK) Study Program at Universitas Kristen Satya Wacana has specific needs for technology usage in learning methods. PTIK students are required not only to master information technology but also to effectively integrate technology into the learning process. This study aims to evaluate the effectiveness of the Flearn application as a learning support tool for PTIK students at Universitas Kristen Satya Wacana. The findings of this study are expected to assess the application usage and user satisfaction with Flearn in the learning process. These results are anticipated to serve as a basis for improving the e-learning platform to achieve optimal performance. Thus, this research contributes to supporting the integration of digital technology in enhancing the quality of education in higher education institutions.